Outcomes of the Warden Procedure for Anomalous Pulmonary Venous Return to the Superior Vena Cava: A 17-Year Experience - Su Chan Lim; Jae Gun Kwak; Sungkyu Cho; Jooncheol Min; Sangjun Lee; Hye Won Kwon; Woong-Han Kim (Journal of Chest Surgery, 2022)
Background: Surgical repair of partial anomalous pulmonary venous return (PAPVR) to the superior vena cava (SVC) using the Warden procedure has favorable outcomes. However, there remain some concerns after the Warden procedure, such as sinoatrial nodal dysfunction and systemic or pulmonary venous stenosis. We investigated the outcomes of the Warden procedure for repair of PAPVR to the SVC. Methods: This retrospective study included 22 consecutive patients who underwent the Warden procedure for PAPVR between 2002 and 2018. The median age and body weight at operation were 27.5 months (interquartile range [IQR], 5.0–56.8 months) and 13.2 kg (IQR, 6.5–16.0 kg), respectively. The median follow-up duration was 6.2 years (IQR, 3.5–11.6 years). Results: There were no cases of early or late mortality. No patients had postoperative heart rhythm problems, except 1 patient who showed transient sinoatrial nodal dysfunction in the immediate postoperative period. Procedure-related complications requiring reintervention occurred in 5 patients, including 3 of 4 SVC stenosis cases and 2 pulmonary venous stenosis cases during follow-up. The rate of freedom from reintervention related to the Warden procedure was 75.9% at 10 years. Conclusion: In cases requiring extension or creation of an atrial septal defect to achieve a sufficient venous pathway, or interposition of an entire circumferential conduit between the SVC and right atrium due to the shortness of the SVC in the Warden procedure, stenotic complications of the venous pathway occurred. Careful observation of changes in the pressure gradient or anatomical stenosis is required in such patients.